Trefoil Factor 3, Cholinesterase and Homocysteine: Potential Predictors for Parkinson’s Disease Dementia and Vascular Parkinsonism Dementia in Advanced Stage - Jing Zou; Zhigang Chen; Caiqian Liang; Yongmei Fu; Xiaobo Wei; Jianjun Lu; Mengqiu Pan; Yue Leon Guo; Xinxue Liao; Huifang Xie; Duobin Wu; Min Li; et al. (2018)
Trefoil factor 3 (TFF3), cholinesterase activity (ChE activity) and homocysteine (Hcy) play critical roles in modulating recognition, learning and memory in neurodegenerative diseases, such as Parkinson's disease dementia (PDD) and vascular parkinsonism with dementia (VPD). However, whether they can be used as reliable predictors to evaluate the severity and progression of PDD and VPD remains largely unknown.We performed a cross-sectional study that included 92 patients with PDD, 82 patients with VPD and 80 healthy controls. Serum levels of TFF3, ChE activity and Hcy were measured. Several scales were used to rate the severity of PDD and VPD. Receivers operating characteristic (ROC) curves were applied to map the diagnostic accuracy of PDD and VPD patients compared to healthy subjects.Compared with healthy subjects, the serum levels of TFF3 and ChE activity were lower, while Hcy was higher in the PDD and VPD patients. These findings were especially prominent in male patients. The three biomarkers displayed differences between PDD and VPD sub-groups based on genders and UPDRS (III) scores' distribution. Interestingly, these increased serum Hcy levels were significantly and inversely correlated with decreased TFF3/ChE activity levels. There were significant correlations between TFF3/ChE activity/Hcy levels and PDD/VPD severities, including motor dysfunction, declining cognition and mood/gastrointestinal symptoms. Additionally, ROC curves for the combination of TFF3, ChE activity and Hcy showed potential diagnostic value in discriminating PDD and VPD patients from healthy controls.Our findings suggest that serum TFF3, ChE activity and Hcy levels may underlie the pathophysiological mechanisms of PDD and VPD. As the race to find biomarkers or predictors for these diseases intensifies, a better understanding of the roles of TFF3, ChE activity and Hcy may yield insights into the pathogenesis of PDD and VPD.